Developing Readiness for Change Through Digital Leadership to Accelerate Digital Transformation MSMEs Seaweed - Wijaya, Andreas (Manajemen dan Bisnis, 2025)
The seaweed bussiness in Indonesia has significant potential to strengthen the national economy. However, in the development of its business, downstream processing has rarely transformed digitally, despite the increasing advancement of digital platforms. Human resource factors hinder this transformation, such as digital skills and literacy, which make people reluctant to change. Therefore, this study will examine the theory of Planned Organizational Change Models in developing change readiness behavior. The research method uses a quantitative approach by distributing questionnaires with a Likert scale of 1-5. The sample in this study consists of workers in the marine industry from small and medium-sized enterprises, totaling 182 people in South Sulawesi, using purposive sampling techniques. The criteria for selecting the sample are units with employees who have been working for at least three years, ensuring they understand the workflow and have a perception of digital transformation. The collected data is processed using SmartPLS. The results of this study show that there is an influence of digital leadership on readiness to change, as well as readiness to change on commitment and behavior supporting change. Therefore, readiness to change is crucial in supporting the success of the transformation.